The Market's Valuation of Nonreported Accounting Measures: Retrospective Reconciliations of Non-U.S. and U.S. GAAP - Rees, Lynn; Elgers, Pieter (Journal of Accounting Research, 1997)
Lynn Rees, Pieter Elgers, The Market's Valuation of Nonreported Accounting Measures: Retrospective Reconciliations of Non-U.S. and U.S. GAAP, Journal of Accounting Research, Vol. 35, No. 1 (Spring, 1997), pp. 115-127